PENGARUH MODEL PEMBELAJARAN TWO STAY TWO STRAY (TSTS) TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPS KELAS IV SD NEGERI KADU SEMPUR - Rusmiati, Sihury Wellya Pamungkas; Latifah, Nur; Fadillah, Ahmad Arif (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
This study aims to determine the effect of the two stay two stray (TSTS) learning model on the learning outcomes of grade IV social studies subjects at SDN Kadu Sempur. This research is quantitative research using quasi-experimental research methods with pretest-postest. The population subjects in this study were grade IV students at SD Negeri Kadu Sempur by taking samples of two classes as many as 32 class IV B students as a control class and 32 grade IV A students as an experimental class. So it can be concluded